Dietary intake and changes in relation to BMI SDS and metabolic measures in a childhood obesity intervention – Finnmark Activity School - Berglund, Thea (UiT Norges arktiske universitet, 2021)
Background: Overweight and obesity in childhood doubles the risk of becoming overweight as an adult, as well as it increases the risk of related comorbidities. Cardiovascular diseases are a consequence of obesity and the most common cause of death worldwide. Diet and physical activity are modifiable causes of overweight. Overweight and obesity should be prevented, but treatment must be optimized as well. Aim/objective: Describe dietary characteristics at baseline and 24-month for children participating in an overweight and obesity intervention. Further, evaluate which dietary changes that are effective for Body Mass Index Standard Deviation Score (BMI SDS) decrease and improvement in metabolic measures. Methods: We used data from Finnmark Activity School (RCT) conducted from 2009-2013. 83 children were eligible for this thesis and included in our analysis. Data were collected through a food frequency questionnaire (FFQ). Anthropometrical and metabolic were measured by standardized methods. Change variables were made for BMI SDS, total cholesterol, LDL-cholesterol, HDL-cholesterol, triglycerides, blood pressure and dietary variables. Baseline characteristics were included to describe participant’s diet at baseline. We analyzed our data as a prospective cohort. Results: Participants diet were overall similar to data from nationwide studies. Mean decrease in BMI SDS were -0.13 units (p=0.006). Total cholesterol decreased by -0.39 mmol/Hg (p=0.001). Intake of snacks and fast-foods statistically significant decreased by 0.75 (p=0.010) and 0.26 times/week (0.036). Linear regression analysis showed no association between dietary change-variables and change in BMI SDS. In addition, no association were found between dietary change-variables and changes in total cholesterol. Logistic regression showed no increased or decreased OR for change in blood-pressure from changes in diet. Conclusion: The decrease in BMI SDS and total cholesterol shows that the intervention was successful. However, due to limitations in our methods ...